(3efgGL GdYGHOjfs - (3eMeO Hf eMeO GdZRGdj, CHh MGeOs ((3MSf GHQGgje GdMfaj GdUaOi s)
(3ChdgG (B:s
(3EYdehG ENhGfj CSYOce Gddg hEjGfG HeQVGJg, Cf GdYHGO KeQI GdYde s
(3BNQgG (B:s
(3OYhGge ajgG SHMGfc Gddge hJMjJge ajgG SdGe hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hBdg CLeYjf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1876s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs